2010
DOI: 10.1039/b9nr00346k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and application of polyaniline nanospheres to biosensing

Abstract: Polyaniline nanospheres (PANI-NS) prepared by morphological transformation of micelle polymerized camphorsulfonic acid (CSA) doped polyaniline nanotubes (PANI-NT) in the presence of ethylene glycol (EG) have been characterized by X-ray diffraction, atomic force microscopy, transmission electron microscopy, scanning electron microscopy, Fourier transform infra-red and UVVisible spectroscopy. A PANI-NS (60-80 nm) film deposited onto an indium-tin-oxide (ITO) coated glass plate by the solution casting method has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 40 publications
2
50
1
1
Order By: Relevance
“…Similarly, Dhand et al have investigated the performance of chemically fabricated PANI nanospheres and electrophoretically deposited nanostructured PANI as platform towards the fabrication of cholesterol biosensor. These studies have revealed that PANI nanospheres show better detection range with faster response time and shelf-life that may be attributed to the large aspect ratio of these films (Dhand et al, 2010). The integration of nanostructures and biomolecules may lead to new hybrid systems that couple the recognition or catalytic properties of biomaterials with attractive electronic and structural characteristics.…”
Section: Pani: An Efficient Materials For Biosensing Applicationmentioning
confidence: 98%
“…Similarly, Dhand et al have investigated the performance of chemically fabricated PANI nanospheres and electrophoretically deposited nanostructured PANI as platform towards the fabrication of cholesterol biosensor. These studies have revealed that PANI nanospheres show better detection range with faster response time and shelf-life that may be attributed to the large aspect ratio of these films (Dhand et al, 2010). The integration of nanostructures and biomolecules may lead to new hybrid systems that couple the recognition or catalytic properties of biomaterials with attractive electronic and structural characteristics.…”
Section: Pani: An Efficient Materials For Biosensing Applicationmentioning
confidence: 98%
“…After this mediator has been immobilized on the electrode surface, LIP and GDH are covalently attached to PANI-SWCNT composite film via amide bond formation between the ÀNHÀ and ÀNH 2 groups of PANI and À COOH group of both the enzymes using EDC as the coupling agent and NHS as the activator (Scheme 1A) [29]. For the enzyme immobilization, the optimal binding is achieved when 50 mL solution of 50 mg LIP and 10 mL solution of 10 mg GDH mixed with 0.4 M EDC and 0.1 M NHS is dropped onto 1 cm 2 of PANI-SWCNT film and kept in a humid chamber for about 4 hours.…”
Section: Immobilization Of Tb Lip and Gdh Onto Pani-swcnt Composite mentioning
confidence: 99%
“…Doping with acid and base can interchange EB and emeraldine salt forms of PANI. EB is regarded as the most useful form of PANI due to its high stability at room temperature and its doped form is electrically conducting [19][20][21]. The conducting polymer of PANI might be greatly applied in many biosensors in virtue of its especial properties such as (1) high surface area and chemical specificities, (2) redox conductivity and polyelectrolyte characteristics, (3) direct and easy deposition on the electrode, (4) long-term environmental stability, and (5) control of thickness and low cost.…”
Section: Introductionmentioning
confidence: 99%